2007
DOI: 10.1093/ps/86.5.835
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of Growth-Correlated Genes Associated with Fatness and Muscle Fiber Traits in Chickens

Abstract: Thirty single nucleotide polymorphisms (SNP) and one 6-bp insertion-deletion (indel) from 8 genes of somatotropic axis were used to study the association with chicken fatness and muscle fibers. The allele frequency difference between Xinghua and White Plymouth Rock chickens was observed, and their effects on fatness and muscle fiber traits were also evaluated by linkage analyses. The G143831A (G+1705A) SNP of the growth hormone (GH) gene was related to fat width, and the G144762A (G+119A) SNP of the GH gene wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 35 publications
1
40
0
4
Order By: Relevance
“…Polymorphism study in the g.565G>A GHR locus found that the AA genotype had the highest frequency (0.726) than the AG (0.172) and GG (0.102) in overall population. Similar result was reported in Vietnamese (0.86, Khoa et al, 2013), Noi (1.00, Khoa et al, 2013), Xinghua (1.00, Lei et al, 2007), and White Plymouth Rock (1.00, Lei et al, 2007) chickens. Ouyang et al (2008) could not detect the g.565G>A GHR polymorphism using DHPLC detection in Leghorn layer, White Recessive Rock broiler, Taihe Silkies, and Xinghua chickens.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Polymorphism study in the g.565G>A GHR locus found that the AA genotype had the highest frequency (0.726) than the AG (0.172) and GG (0.102) in overall population. Similar result was reported in Vietnamese (0.86, Khoa et al, 2013), Noi (1.00, Khoa et al, 2013), Xinghua (1.00, Lei et al, 2007), and White Plymouth Rock (1.00, Lei et al, 2007) chickens. Ouyang et al (2008) could not detect the g.565G>A GHR polymorphism using DHPLC detection in Leghorn layer, White Recessive Rock broiler, Taihe Silkies, and Xinghua chickens.…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, in the F2 population generated from White Recessive Rock and Xinghua chicken, 18 chickens with the AA genotype were found from total 451 chickens (AA genotype freq= 0.04; Nie et al, 2005). Higher GG genotype frequency was also reported by Lei et al (2007) in Xinghua (0.67) and White Plymouth Rock (1.00) chickens, Zhang et al (2007) forward and reverse primer annealing positions; bold shows Eco72I restriction sites; 499 box shows G565A SNP target (GenBank accession number: AJ506750.1). 500 maturity in semi-intensive rearing system (Yuwanta & Fujihara, 2000).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Compared to other animals, the intron regions of the cGH gene is highly polymorphic. Furthermore, studies using RFLP have shown that these polymorphisms are associated with abdominal fat, egg production, resistance to Marek's disease or avian leucosis, and meat yield traits (Fotouhi et al, 1993;Kuhnlein et al, 1997;Feng et al, 1997;Yan et al, 2003;Lei et al, 2007;Zhang et al, 2007;Xu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Genotyping using PCR-RFLPs method were performed in various populations of Chinese native chickens and it was recommended that an allele present in intron 1 might be linked to laying performance (17). In other animals, growth hormone gene polymorphisms have been reported, for example a polymorphism observed in intron 3 of bovine growth hormone (bGH) gene was found to be linked to milk protein content (14). In fact, regulatory elements have been identified in the intron region of the GH gene in various animals (19).…”
Section: Discussionmentioning
confidence: 99%